Transparansi dan Akuntabilitas Organisasi Pengelola Zakat (OPZ) untuk Mengurangi Tingkat Kemiskinan melalui Perspektif Kelembagaan Islam - Nabillah, Anggia Putri; Utami, Niken Tri; Silalahi, Yuliana (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, Semarang, 2022)
Indonesia is one of the most populous country in this world with total population is about 273.87 million at the end of 2021. among that total popilation, there are still 26.50 million is in below poverty line. As a country with Muslim majority population, Indonesia has one of the potentials that can be optimised to reduce poverty, namely zakat. However, the magnitude of the potential for zakat in realization is still has many obstacles that leads to lower relatization of zakat compared to huge potency of the zakat. Therefore, the main function of zakat to alleviate poverty level cannot be optimised. This study aims to propose the solutions to increase the transparancy and accountability for zakat management organization (OPZ) using an Islamic institutional perspective. Theapproach used in this research is a qualitative research through systematic literature review. The results show that transparency and accountability can be improved by implementing the basic axioms of islamic business ethics, namely balance/fairness in implementing zakat collection activities.